PENDAMPINGAN PEWARNAAN BATIK SINGONEGORO MENGGUNAKAN PEWARNA ALAMI DARI TANAMAN INDIGOFERA TINCTORIA - Widowati Widowati; Nikmatul Khoiriyah; Ana Arifatus Sa’diyah (Universitas Mataram, 2023)
Indonesia has a noble cultural heritage of using safe natural dyes and compounds that are beneficial to the body. Indonesia also has natural wealth and biodiversity which are raw materials for making natural substances. This activity aims to: increase community knowledge and skills about eco-printing textile craft techniques, increase community knowledge and skills about naturally dyed tie-dye textile craft techniques, increase community knowledge and skills about naturally dyed screen printing textile craft techniques, and increase knowledge and skills the community about the utilization of natural dye source plants to become natural coloring pastes. Training and assistance in the use of natural dye applications in the batik business are carried out through several effective methods. Community service activities are carried out using the workshop method or hands-on training, counseling and presentations, and technical guidance. The results of training and mentoring in the use of natural dye applications in batik businesses are very positive and have broad implications, both for the batik business itself, as well as for the environment and surrounding communities.